Osteoid osteoma - A literature review - Migiel, Marcin; Brynczka, Izabela; Siuta, Natalia; Rypel-Bośka, Joanna; Miaśnikiewicz, Jakub; Goleniewska, Klaudia; Stupecka, Aleksandra; Cecuła, Wiktoria; Ciechomski, Kamil (Quality in Sport, 2025)
Introduction and purpose Osteoid osteoma is a benign osteogenic tumor most commonly diagnosed in adolescents and young adults, predominantly males. It typically presents with nocturnally exacerbated bone pain responsive to NSAIDs, attributed to prostaglandin overproduction within the nidus. This review aims to synthesize current knowledge on the clinical presentation, diagnosis, classification, and management strategies for osteoid osteoma. State of knowledge: Although small in size, osteoid osteomas often cause significant morbidity due to intense, localized pain. Conventional radiographs may be inconclusive, especially in atypical cases, necessitating the use of computed tomography as the diagnostic gold standard. Advances in image-guided therapies have largely replaced traditional surgery. Radiofrequency ablation (RFA) has become the first-line treatment due to its high success rate, low recurrence, and rapid functional recovery. Alternative modalities like cryotherapy and laser ablation are effective in select scenarios. Materials and methods: A review was conducted using PubMed and Google Scholar databases, concerning osteoid osteoma published between 2000 and 2024. Conclusions: Osteoid osteoma is a curable condition with excellent prognosis when appropriately managed. Accurate diagnosis and tailored intervention—particularly with minimally invasive techniques—enable full symptom resolution in most patients.